A Scope Argument against T‐to‐C Movement in Sluicing. (29th July 2020) - Landau, Idan
Abstract: Most accounts of sluicing assume it is derived by TP deletion at PF; however, C′ deletion is a viable option, which is even better equipped to explain the Sluicing–Comp Generalization. Nonetheless, this article shows that C′ deletion must be rejected, because it predicts scope enhancement for modals that raise to C in sluicing when in fact they take scope in T or below it. An implication is that some independent principle must block T‐to‐C movement under sluicing. The results further confirm that head movement must be a syntactic operation insofar as it affects semantic interpretation.